Effect of Reward Satisfaction on Job Performance: Employee Perspectives - Shrestha, Prakash; Chhetri, Guna Raj; Khadka, Keshab (Jana Adarsha Research Journal, 2025)
The purpose of this study is to analyze the effect of reward satisfaction on job performance of employees. This research employs a descriptive research design. A total of 350 questionnaires were distributed to seven insurance companies. The findings demonstrate a significant association between pay level satisfaction and job performance. They also show that salary administration has an important and positive effect on job performance. The findings indicate that raise satisfaction has a favorable and significant impact on job performance. They also demonstrate a positive and significant effect of benefits satisfaction on employee job performance. In fact, employee satisfaction with organizational rewards has a significant and favorable effect on job performance. Organizational rewards, both intrinsic (recognition, career growth chances) and extrinsic (bonuses, raises), have the potential to greatly increase enthusiasm. When employees believe their efforts are recognized and rewarded, they are more motivated to perform effectively. Rewards make employees feel valued and appreciated, which leads to increased job satisfaction. Employees who are satisfied with their rewards are more likely to be engaged and committed to their jobs. Therefore, today’s organizations must focus on effective rewards that satisfy employees and effectively improve their performance levels.